Analysis of Abrasive Materials dan Air Pressure Variations for Thermal Spray Aluminum Coating on Adhesion Strength and Corrosion Resistance in Seawater Environment - Herman Pratikno; Raymond Danielle Mulya; Wimala Lalitya Dhanistha (Department of Ocean Engineering, 2025)
Marine structures must withstand the marine environment for a certain design life. However, corrosion causes a decrease in structural integrity before reaching the design life. Thermal spray aluminum coating becomes a protection method because of its resistance to corrosion in the long term. This study analyzed the effect of variations in abrasive materials and air pressure on thermal spray aluminum coating on ASTM A36 steel. The steel material will be blasted with two types of abrasive materials, namely garnet and aluminum oxide, then coated using the electric arc wire spray method at pressures of 2.5 bar, 3.5 bar, and 4.5 bar. Testing was carried out using the pull-off adhesion test and the three-electrode cell method. The results showed that the highest adhesion strength of 12.2 MPa occurred at 4.5 bar aluminum oxide, while the lowest was 6.3 MPa at 2.5 bar garnet. The lowest corrosion rate of 0.001 mm/year was obtained at 4.5 bar garnet, and the highest was 0.101 mm/year at 2.5 bar aluminum oxide. Based on the results of the corrosion rate test, it can be concluded that the increase in pressure is directly proportional to the increase in coating performance in resisting corrosion. Conversely, the increase in surface roughness is inversely proportional to the coating performance in resisting corrosion.